MAKNA KARYA UMBUL DONGA DALAM PELEPASAN WISUDAWAN FAKULTAS SENI PERTUNJUKAN ISI SURAKARTA PERIODE II 15 OKTOBER 2019 - Wardhani, Chrysnanda Kusuma (Greget: Jurnal Kreativitas dan Studi Tari, 2024)
This research is aimed to describe the form and content of Umbul Donga on the Second Period of Graduation Ceremony of The Performing Arts Faculty in the Indonesian Institute of the Arts, Surakarta which was held on October, 15th 2019. This research was done by employing qualitative methods with descriptive narrative analysis and holistic criticism of dance performance by Sutopo. There were several research steps done to accurately collect the data. Data was collected through various sources of references, interviews, and audio-visual records. Sources of references are employed to understand the concept, notion, and background that are correlated with the essence of this research. Furthermore, those are complemented by employing interviews with people who were involved in the Graduation Ceremony of The Performing Arts Faculty at The Indonesian Institute of Arts that was held on October, 15th 2019. The form analysis was done by using Speech Act Theory by Kreidler. Umbul Donga is constructed of two elements (verbal and nonverbal elements). Those are supported by the Performing Arts Theory by Maryono. The Performing Arts Theory was employed to explain non-verbal components which consist of themes, movements, dancers, expressions, floor patterns, makeups, and music.  It was found that based on the verbal and nonverbal analysis, work conception, and audience feedback, Umbul Donga on the Second Period of Graduation Ceremony of The Performing Arts Faculty in the Indonesian Institute of the Arts, Surakarta which was held on October, 15th 2019 can be interpreted as a medium of pray forgiveness, gratitude, and guidance.